2009
DOI: 10.1177/0018726708101989
|View full text |Cite
|
Sign up to set email alerts
|

Managing difference in feminized work: Men, otherness and social practice

Abstract: The paper presents a qualitative study of men who do traditionally female dominated and feminized work (specifically nursing and primary school teaching). Men are often seen as not only a minority to women in these contexts, but also their Other. The paper explores the processes of doing gender as a social and discursive practice, highlighting the necessity to manage difference and the processual, emergent, dynamic, partial, and fragmented nature of gendered identities. We show some of the complex ways in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(175 citation statements)
references
References 63 publications
4
165
0
6
Order By: Relevance
“…Thus, social norms provide feelings of connectedness because conforming to norms results in attaining a positive and valued social identity and leads to a sense of belonging (Smith & Mackie, 2007). In addition, our sense of self identity is formed by comparing ourselves to others and understanding sameness and difference-what we are and what we are not (Pullen & Simpson, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, social norms provide feelings of connectedness because conforming to norms results in attaining a positive and valued social identity and leads to a sense of belonging (Smith & Mackie, 2007). In addition, our sense of self identity is formed by comparing ourselves to others and understanding sameness and difference-what we are and what we are not (Pullen & Simpson, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Adopting an interpretative approach this study assumes that gender is socially constructed, a perspective adopted in similar studies, for example Pullen andSimpson (2009), andKelan (2008). Accordingly, a qualitative approach enabled respondents to provide rich descriptions of their experiences (Richards, 1999), while providing scope for the researcher to pursue interesting lines of reasoning (Johnson and Turner, 2003).…”
Section: The Current Studymentioning
confidence: 99%
“…Van Den Brink, Benschop and Jansen's (2010) study of 13 universities in the Netherlands also revealed a range of casual discriminatory practices in the appointment of professors that eluded formal protocols and objective criteria. The local logic of the institution and the organisational status quo are often informally invoked to determine who might be a comfortable fit (Grummell, Devine and Lynch 2009;Pullen and Simpson 2009). In our study, a common complaint related to the political allegiance involved in recruitment and also how the process was invariably male-dominated.…”
Section: Also In Sri Lanka This Administration Is Somehow a Dirty Gammentioning
confidence: 99%